Ethylene and 1-MCP treatments involved in differential expression of signal transduction and ethylene biosynthesis genes in Dendrobium cut flowers during senescence - Thanomchit, Kanokwan; Kasemsap, Poonpipope; Imsabai, Wachiraya; Burns, Parichart; Mongkolchaiyaphruek, Anchaya (วารสารแก่นเกษตร, 2024)
Dendrobium orchids represent a significant portion of Thailand’s cut flower exports, with their longevity being influenced by ethylene sensitivity. This research aimed to elucidate the regulatory mechanisms of ethylene and its inhibitor, 1-methylcyclopropene (1-MCP), on the premature senescence of Dendrobium ’Khao Chaimongkol’ cut flowers at different developmental stages. Using a combination of treatments, the inflorescences were treated with 500 nL.L-1 1-MCP, 0.4 µL.L-1 ethylene, and a combination of 500 nL.L-1 1-MCP followed by 0.4 µL.L-1 ethylene. Senescence symptoms and gene expression profiles related to ethylene signaling pathways and ethylene biosynthesis were assessed in both floral buds and open florets, for five days. The results indicated that ethylene-treated inflorescences rapidly displayed senescence symptoms, with the first visible signs being venation followed by drooping within a day. Exogenous ethylene triggered the upregulation of ethylene receptors ERS1, signal transduction genes CTR1, EIL1, and ERF1, and stimulated the expression of ACS1 and ACO1 genes responsible for ethylene production in floral buds. In contrast, in open florets, exogenous ethylene upregulated ERS1, CTR1, and ACO1 expression but did not induce EIL1, ERF1, and ACS1. Consequently, floral buds exhibited more pronounced premature senescence compared to open florets. This differential response indicated distinct effects of exogenous ethylene on ethylene signaling transduction between floral buds and open florets. Conversely, the application of 1-MCP led to competitive binding of ethylene receptors, resulting in the suppression of ERS1, CTR1, EIL1, ERF1, and ACO1 expression in floral buds. In open florets, however, 1-MCP did not suppress the expression of EIL1, ERF1, and ACS1. Consequently, premature senescence was inhibited in both floral buds and open florets. This differential response indicated distinct mechanism effects of ethylene and 1-MCP on ethylene signaling pathway across the differential sensitivity of floral tissues and developmental stages to ethylene.